Post-Memory and Family Bonds: Trauma Transmission in the Orphan Train Narrative - Ulfah, Helmatun Fauza (Muadalah, 2024)
The concept of post-memory, introduced by Marianne Hirsch, offers a framework for understanding how collective memory is transmitted across generations. This study examines intergenerational trauma through a qualitative descriptive analysis of Christina Baker Klein's novel Orphan Train. It focuses on Vivian Daly’s traumatic experiences as an orphan train rider and their impact on her identity and familial memory. The research aims to explore how Vivian’s past shapes her understanding of her history, her role within her family narrative, and how family narratives and inherited objects contribute to preserving memory and transmitting trauma intergenerationally. Findings reveal that family narratives and objects play a critical role in maintaining memory and shaping familial identity. These elements not only preserve individual experiences but also act as conduits for transmitting collective trauma across generations. Contextually, this study highlights the broader relevance of post-memory in social situations such as migration or cultural conflict, where trauma influence’s identity formation and community ties. By situating its findings within the discourse on collective memory and trauma, this research contributes to understanding how personal and familial histories intersect to shape intergenerational identities. This study underscores the importance of considering intergenerational trauma in analysing collective memory processes. Keywords: Collective Memory; Family Narratives; Intergenerational Trauma; Post-Memory